Toward an improved understanding of the Southern Ocean's biological pump: phytoplankton group-specific contributions to nitrogen and carbon cycling across the Subantarctic Indian Ocean - Forrer, Heather (Department of Oceanography, 2021)
Iron (and silicate) (co-)limitation of phytoplankton is considered a primary cause of the Southern Ocean's inefficient biological pump. However, the role of phytoplankton community structure and response to nutrient cycling remains poorly understood. In a mass balance sense, phytoplankton consumption of new nitrogen (N; e.g., allochthonous nitrate) is proportional to net carbon (C) export, while growth fueled by recycled N (e.g., ammonium) yields no net C flux. The N isotope ratio (δ15N) of surface biomass has long been used as an integrative tracer of new versus regenerated uptake. This approach is rendered more accurate by coupling either fluorescence-activated cell sorting (FACS; of nano- and picophytoplankton; 0.4-20 μm) or microscopy (for microphytoplankton; >20 um) with groupspecific δ15N measurements. Samples were collected for the analysis of nutrients and nitrate-, FACS-, and microscopy-δ15N on a mid-summer transect of the Subantarctic Indian basin during the 2016/17 Antarctic Circumnavigation Expedition (ACE) cruise. The data show that all phytoplankton populations preferentially utilize nitrate (≥55%) across the Indian Sector of the Subantarctic, potentially driving higher C export potential than previously estimated. Indeed, near the Subantarctic islands, 72% of microand >80% of nano- and picophytoplankton growth is supported by nitrate. This is likely due to the partial alleviation of phytoplankton iron and silicate stress, largely as a result of bathymetric upwelling, which constitutes a manifestation of the island mass effect. C export potential is lower in the open ocean region away from the islands where iron stress has been shown to be higher; here, nitrate supports >55% of micro- and picophytoplankton and 7 to 79% of nanophytoplankton growth. In terms of relative abundance (RA), the open Subantarctic is dominated by picoeukaryotes (64%), although there exists a large disconnect between relative abundance and potential contribution to C export. The three largest surface-ocean phytoplankton populations included in this study – microphytoplankton, cryptophytes, and nanoeukaryotes – each contribute ~30% to the total C export potential across the Subantarctic Indian sector while picophytoplankton contribute ~5%. Thus, as has been concluded previously, the larger phytoplankton size classes are disproportionately important drivers of the Subantarctic biological pump. Other interesting ecological findings include diatom-dominated microphytoplankton populations apparently fueled by a significant fraction of regenerated N, even in areas of iron supply, and Synechococcus relying near-exclusively on new N, in contrast to subtropical observations. Additionally, the abundance of Synechococcus appears to be controlled by the availability of iron across the Subantarctic, with silicate and temperature playing a supporting role.